Pre-phase treatment with rituximab and high-dose methotrexate to re-evaluate eligibility for intensive induction treatment of frail patients with central nervous system lymphoma - Julia Wendler; Richard I. Lewis; Alexandra Kutilina; Markus Knott; Lisa Kristina Isbell; Elke Valk; Peter Borchmann; Jan-Michel Heger; Gerald Illerhaus; Elisabeth Schorb (Haematologica)
Not available.